EFFICACY OF L-ORNITHINE L-ASPARTATE IN PATIENTS WITH ESOPHAGEAL VARICEAL BLEEDING - Petrushenko, V.V.; Grebeniuk, D.I.; Lonskii, K.L.; Gladkykh, V.Y.; Kedyk, O.O.; Rosha, L.H. (World of Medicine and Biology, 2021)
The study analyzed the effectiveness of L-Ornithine L-Aspartate in patients with esophageal variceal bleeding. The study included 67 patients with a confirmed diagnosis of liver cirrhosis complicated by portal bleeding. The experimental group consisted of patients who, in addition to complex treatment in order to maintain liver function, were prescribed intravenous L-Ornithine L-Aspartate with subsequent change to oral administration. The comparison group included patients who did not receive this drug. To assess the effectiveness of treatment, general clinical indices, biochemical indices of the functional state of the liver, indices of quality of life were studied. The use of this drug made it possible to shorten the length of hospital stay and significantly faster improve the main clinical and laboratory indices of the functional state of the liver and the quality of life of patients.
Keywords: L-Ornithine L-Aspartate; liver cirrhosis; esophageal variceal bleeding; quality of life